A comparative study of boron and arsenic (III) rejection from brackish water by reverse osmosis membranes - Teychene, B.; Collet, G.; Gallard, H.; Croue, Jean-Philippe (2013)
This study aims to compare at lab-scale the rejection efficiency of several reverse osmosis membranes (RO) toward arsenic (III) and boron during the filtration of a synthetic brackish water. The effect of pH and operating conditions on the rejection of each RO membrane was studied. Two types of membrane were investigated: “brackish water” and “sea water” membranes.Our results showed that the metalloid rejection depends on the membrane type, pH and transmembrane pressure applied. Increasing pH above the dissociation constant (pKa) of each specie improves significantly the metalloid rejection by RO membranes, whatever the membrane type. Moreover, at identical operating conditions (pH, transmembrane pressure), results showed that the brackish water membranes have a higher water flux and exhibit lower metalloid rejection. The highest As(III) rejection value for the tested brackish water membranes was 99% obtained at pH = 9.6 and 40 bars, whereas it was found that the sea water RO membranes could highly reject As(III), more than 99%, even at low pH and low pressure (pH = 7.6 and 24 bars).Regarding Boron rejection, similar conclusions could be drawn. The sea water RO membranes exert higher removal, with a high rejection value above 96% over the tested conditions. More generally, this study showed that, whatever the operating conditions or the tested membranes, the boron and As(III) permeate concentrations are below the WHO guidelines. In addition, new data about the boron and arsenic permeability of each tested RO membrane was brought thanks to a theoretical calculation.